(untitled) (Harmoni, 2016)
As a multireligious country, Indonesia is facing the dynamic relation between majority and minority: between tension and harmony too. The potrait of Muslim- Buddhist relation in Panggang,Gunung Kidul, as historically observed, has shown a harmonious and unique interaction. This research tries to elaborate this condition. Through literature study, interview and observation, this research found that Muslim-Buddhist have a common basic need to build harmony, and they also have theological fundamental reason and strongly hold ΓÇ£cultural bondsΓÇ£ of the ancient Java between them. There are also associational bond among lay people in society such as social gathering ΓÇ£sepuluhanΓÇ¥ and volley ball team; and practising quotidian bond such as eating gathering in ΓÇ£sedekah bumiΓÇ¥ and working together in ΓÇ£sambatanΓÇ¥. Those social bonding in each group does not bring to exclusivism but sthrengten their existence to hold mutual goals.